Using properties of determinants, prove that:
$\left|\begin{array}{lll}x & x^{2} & 1+p x^{3} \\ y & y^{2} & 1+p y^{3} \\ z & z^{2} & 1+p z^{3}\end{array}\right|=(1+p x y z)(x-y)(y-z)(z-x),$ where $p$ is any scalar.
$\Delta=\left|\begin{array}{lll}x & x^{2} & 1+p x^{3} \\ y & y^{2} & 1+p y^{3} \\ z & z^{2} & 1+p z^{3}\end{array}\right|$
Applying $R_{2} \rightarrow R_{2}-R_{1}$ and $R_{3} \rightarrow R_{3}-R_{1},$ we have:
$\Delta=\left|\begin{array}{ccc}x & x^{2} & 1+p x^{3} \\ y-x & y^{2}-x^{2} & p\left(y^{3}-x^{3}\right) \\ z-x & z^{2}-x^{2} & p\left(z^{3}-x^{3}\right)\end{array}\right|$
$=(y-x)(z-x)\left|\begin{array}{ccc}
x & x^{2} & 1+p x^{3} \\
1 & y+x & p\left(y^{2}+x^{2}+x y\right) \\
1 & z+x & p\left(z^{2}+x^{2}+x z\right)
\end{array}\right|$
Applying $R_{3} \rightarrow R_{3}-R_{2},$ we have:
${\Delta = (y - x)(z - x)\left| {\begin{array}{*{20}{c}}
x&{{x^2}}&{1 + p{x^3}} \\
1&{y + x}&{p\left( {{y^2} + {x^2} + xy} \right)} \\
0&{z - y}&{p(z - y)(x + y + z)}
\end{array}} \right|}$
${ = (y - x)(z - x)(z - y)\left| {\begin{array}{*{20}{c}}
x&{{x^2}}&{1 + p{x^3}} \\
1&{y + x}&{p\left( {{y^2} + {x^2} + xy} \right)} \\
0&1&{p(x + y + z)}
\end{array}} \right|}$
Expanding along $R_{3},$ we have:
$\Delta=(x-y)(y-z)(z-x)\left[(-1)(p)\left(x y^{2}+x^{3}+x^{2} y\right)\right.$ $\left. { + 1 + p{x^3} + p(x + y + z)(xy)} \right]$
$ = (x - y)(y - z)(z - x)$ $\left[ { - px{y^2} - p{x^3} - p{x^2}y} \right.\left. { + 1 + p{x^3} + p{x^2}y + px{y^2} + pxyz} \right]$
$ = (x - y)(y - z)(z - x)(1 + pxyz)$
Hence, the given result is proved.
If $\omega $ is a complex cube root of unity, then the determinant $\left| {\,\begin{array}{*{20}{c}}2&{2\omega }&{ - {\omega ^2}}\\1&1&1\\1&{ - 1}&0\end{array}\,} \right| = $
The value of $\sum\limits_{n = 1}^N {{U_n},} $ if ${U_n} = \left| {\,\begin{array}{*{20}{c}}n&1&5\\{{n^2}}&{2N + 1}&{2N + 1}\\{{n^3}}&{3{N^2}}&{3N}\end{array}\,} \right|$ is
Without expanding, prove that $\Delta=\left|\begin{array}{ccc}x+y & y+z & z+x \\ z & x & y \\ 1 & 1 & 1\end{array}\right|=0$
If $f(x) = \left| {\begin{array}{*{20}{c}}{x - 3}&{2{x^2} - 18}&{3{x^3} - 81}\\{x - 5}&{2{x^2} - 50}&{4{x^3} - 500}\\1&2&3\end{array}} \right|$ then $f(1).f(3) + f(3).f(5) + f(5).f(1)$=